Identifying molecular phenotype of nucleus pulposus cells in human intervertebral disc with aging and degeneration. Issue 8 (13th April 2016) - Tang, Xinyan; Jing, Liufang; Richardson, William J.; Isaacs, Robert E.; Fitch, Robert D.; Brown, Christopher R.; Erickson, Melissa M.; Setton, Lori A.; Chen, Jun
ABSTRACT: Previous study claimed that disc degeneration may be preceded by structure and matrix changes in the intervertebral disc (IVD) which coincide with the loss of distinct notochordally derived nucleus pulposus (NP) cells. However, the fate of notochordal cells and their molecular phenotype change during aging and degeneration in human are still unknown. In this study, a set of novel molecular phenotype markers of notochordal NP cells during aging and degeneration in human IVD tissue were revealed with immunostaining and flow cytometry. Furthermore, the potential of phenotype juvenilization and matrix regeneration of IVD cells in a laminin‐rich pseudo‐3D culture system were evaluated at day 28 by immunostaining, Safranin O, and type II collagen staining. Immunostaining and flow cytometry demonstrated that transcriptional factor Brachyury T, neuronal‐related proteins (brain abundant membrane attached signal protein 1, Basp1; Neurochondrin, Ncdn; Neuropilin, Nrp‐1), CD24, and CD221 were expressed only in juvenile human NP tissue, which suggested that these proteins may be served as the notochordal NP cell markers. However, the increased expression of CD54 and CD166 with aging indicated that they might be referenced as the potential biomarker for disc degeneration. In addition, 3D culture maintained most of markers in juvenile NP, and rescued the expression of Basp1, Ncdn, and Nrp 1 that disappeared in adult NP native tissue. These findings provided new insight into molecular profile that may be used to characterize the existence of a unique notochordal NP cells during aging and degeneration in human IVD cells, which will facilitate cell‐based therapy for IVD regeneration. © 2016 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 34:1316–1326, 2016.